EFEKTIVITAS PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA MATERI MATEMATIKA KELAS VII - Sri Satriani; Randy Saputra Mahmud; Isnawati Isnawati (Delta: Jurnal Ilmiah Pendidikan Matematika, 2019)
The aims of this study to know the effectiveness of think pair share cooperative model toward the mathematics learning outcomes for students in class VIIIB SMPN 3 Sungguminasa. This research was a pre-experimental research, the design was anone group pretest-posttest which involved in one class during 5 meetings. The learning achievement test, student activity observation, and student questionnaire responses were applied for collecting data.The data analyzed by descriptive and inferensial technique.The results showed that the average score of learning outcomes before being taught mathematics learning with the application of think pair share cooperative model was 37.10 with standard deviation 12,169, which showed that completeness classically was not achieved, while the average score the average mathematics learning outcomes of students after being taught mathematics learning with the application of the think pair share cooperative model was 84.17 with standard deviation 67.57 having achieved classical completeness with a normalized gain value of 0.73 being in the high category. Student activities in the active category where the average percentage 82.49%. Student positive responses showedthe average percentage was 94.29%. Based on these results it can be concluded that mathematics learning through the application of think pair share cooperative model in class VIIB SMPN 3 Sungguminasaapplied effectively.